The president and immigration law - Cox, Adam; 1973- (Oxford University Press, 2020)
On February 15, 2019, President Donald Trump declared a national emergency at America's southern border. He depicted a dire crisis, with criminals and drugs flowing unchecked into the country, unlawful border crossers overwhelming enforcement capacity, and dangerous immigrants disappearing into the nation's interior after being released from detention. With his presidential proclamation, he ordered the military to assist in hardening the border, and he declared his intent to re-direct billions of dollars to build the wall he had promised since he first announced his candidacy. In a striking rebuke, Congress voted to overturn the President's declaration of emergency. Never before had Congress rejected a president's proclamation under the National Emergencies Act. Some members decried the President's move as an unlawful usurpation of Congress's power of the purse. Congress had just rejected the administration's request for funds to build a border wall. In trying nonetheless to re-allocate military funding to the project, critics contended, the President displayed contempt for Congress's constitutional authority to appropriate federal dollars. Many representatives argued further that the President had manufactured the crisis, emphasizing that adding an exceedingly expensive wall to already ample enforcement would not address the real problems at the border. Illegal crossings, they noted, had been declining for over a decade and were at historic lows during the President's first two years in office. The types of migrants now arriving at the border presented urgent legal and policy concerns, but not the threat the President imagined. They were families fleeing violence in Central America. They often sought out border patrol agents at ports of entry in order to request asylum, rather than cross through the desert to evade apprehension. A new wall would not stop them. President Trump promptly issued the very first veto of his administration and attempted to press forward with his plans. His clash with Congress was partly about partisan disagreement. It reflected the deep gulf that now separates the Democratic and Republican parties on immigration policy. But even the Republican-controlled Senate voted to reject the President's emergency declaration. "The Senate vote," the Washington Post remarked the following day, "stood as a rare instance of Republicans breaking with Trump in significant numbers on an issue central to his presidency." It remains to be seen whether the President or Congress will emerge with the upper hand; as we go to press, the funding fight remains tied up in the courts. But the unfolding conflict has transcended partisanship, pitting Congress against the Executive in a battle for control of immigration policy"--